1998
DOI: 10.1046/j.1365-2796.1998.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol inhalation has no effect on myocardial ischaemia, arrhythmias and heart‐rate variability in patients with coronary artery disease plus asthma or chronic obstructive pulmonary disease

Abstract: The commonly used doses of inhaled or nebulized salbutamol induced no acute myocardial ischaemia, arrhythmias or changes in heart rate variability in patients with CAD and clinically stable asthma or COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Two-week salbutamol treatment increased baseline LF variability and LF/ HF variability ratio of ECG R-R intervals when compared to the placebo treatment. However, different results were obtained by Rossinen et al [20] who reported the commonly used doses of inhaled or nebulized salbutamol induced no acute myocardial ischaemia, arrhythmias or changes in HRV as assessed by Holter monitoring of 24 patients with coronary artery disease and clinically stable asthma or chronic obstructive pulmonary disease. A 4-week salmeterol treatment increased baseline HR, LF/HF variability ratio of R-R intervals.…”
Section: Discussionmentioning
confidence: 81%
“…Two-week salbutamol treatment increased baseline LF variability and LF/ HF variability ratio of ECG R-R intervals when compared to the placebo treatment. However, different results were obtained by Rossinen et al [20] who reported the commonly used doses of inhaled or nebulized salbutamol induced no acute myocardial ischaemia, arrhythmias or changes in HRV as assessed by Holter monitoring of 24 patients with coronary artery disease and clinically stable asthma or chronic obstructive pulmonary disease. A 4-week salmeterol treatment increased baseline HR, LF/HF variability ratio of R-R intervals.…”
Section: Discussionmentioning
confidence: 81%
“…Indirect evidence from four of the studies examining the impact of inhaled beta-2 agonist treatment in patients with chronic heart failure showed improved pulmonary function relative to placebo (8,9,11,12). Ng et al demonstrated a 6% improvement in FEV 1 (forced expiratory volume in the first second), and Rossinen et al showed a statistically significant increase in peak expiratory flow from 410 to 450 L/min (8,9). Uren et al demonstrated a statistically significant increase in FEV 1 from 2.28 to 2.38 L (11).…”
Section: Effect Of Acutely Delivered Beta-2 Agonists On Pulmonary Funmentioning
confidence: 99%
“…However, there is no evidence in the studies reviewed to suggest that acute beta-2 agonist administration increases or worsens myocardial ischemia, either from direct evidence in patients with ADHF or from indirect evidence in patients with chronic heart failure, and no electrocardiographic changes suggestive of ischemia were observed (8,9,15,18,20,22,23,25,26,28). In fact, Dawson et al showed that when albuterol was administered to 31 patients with myocardial infarction and cardiogenic shock, hemodynamics improved and no subject developed worsening ischemia (20).…”
Section: Effects Of Beta-2 Agonists In Heart Failure Patients With Acmentioning
confidence: 99%
“…The criteria for exclusion were use of medication, anything other than the usual types of asthma medication during the previous 4 weeks (common antiasthma agents, e.g. beta-2 agonists such as salbutamol, do not influence heart rate variability [27]), psychosis, severe anxiety and/or depression, substance abuse, the current use of psychotropic medication [cf. [28,29,30] or psychotherapy as well as smoking and hypertension.…”
Section: Methodsmentioning
confidence: 99%